Muslim Secular Democracy - Rahim, Lily Zubaidah. author. aut Link
XIII, 284 p. 4 illus.
Keywords: The book offers a nuanced and innovative analyses of the emergence of an inclusive secular democratic state paradigm which incorporates the sacred within the framework of secular democracy in the Muslim World.